2010
DOI: 10.1186/1472-6831-10-3
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Indigenous Australian oral health literacy and self-reported oral health outcomes

Abstract: ObjectivesTo determine oral health literacy (REALD-30) and oral health literacy-related outcome associations, and to calculate if oral health literacy-related outcomes are risk indicators for poor self-reported oral health among rural-dwelling Indigenous Australians.Methods468 participants (aged 17-72 years, 63% female) completed a self-report questionnaire. REALD-30 and oral health literacy-related outcome associations were determined through bivariate analysis. Multivariate modelling was used to calculate ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
141
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(164 citation statements)
references
References 24 publications
10
141
1
Order By: Relevance
“…Strait Islander people is limited to a few studies identifying an association between inadequate dental health literacy and poorer dental health outcomes among Aboriginal Australians residing in rural South Australia (Jamieson et al 2008;Parker and Jamieson 2010;Jamieson et al 2013). Assessment of health literacy will provide some indication of the prevalence of adequate health literacy, increase health professionals' awareness of the need to provide health information that is easily understood by patients and assist Indigenous Australians to better manage their illness.…”
Section: Information On Health Literacy Among Aboriginal and Torresmentioning
confidence: 99%
“…Strait Islander people is limited to a few studies identifying an association between inadequate dental health literacy and poorer dental health outcomes among Aboriginal Australians residing in rural South Australia (Jamieson et al 2008;Parker and Jamieson 2010;Jamieson et al 2013). Assessment of health literacy will provide some indication of the prevalence of adequate health literacy, increase health professionals' awareness of the need to provide health information that is easily understood by patients and assist Indigenous Australians to better manage their illness.…”
Section: Information On Health Literacy Among Aboriginal and Torresmentioning
confidence: 99%
“…Accumulating evidence suggests that health literacy also has a pivotal role in the context of oral health (Horowitz and Kleinman, 2008;Parker and Hernandez, 2012). Recent studies have detected links between lower literacy and poor outcomes in the domains of oral health status (Parker and Jamieson, 2010;Lee et al, 2012;Wehmeyer et al, 2013), knowledge (Macek et al, 2010), and quality of life .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies suggest that health literacy is associated with educational attainment in self-rated health and in regular dental attendance pattern among older adults (Bennett et al, 2009). In addition, oral health literacyrelated outcomes are risk indicators for poor self-reported oral health among rural-dwelling Indigenous Australians (Parker & Jamieson, 2010). We found that adults who were married were more likely to report good SROH.…”
Section: Discussionmentioning
confidence: 67%